Ethnic Inequalities in Rectal Cancer Care in a Universal Access Healthcare System: A Nationwide Register-Based Study. Issue 6 (June 2016) - Elferink, Marloes A. G.; Lamkaddem, Majda; Dekker, Evelien; Tanis, Pieter J.; Visser, Otto; Essink-Bot, Marie-Louise
Abstract : BACKGROUND: Ethnic inequalities in colorectal cancer care were reported previously in the United States. Studies specifically reporting on ethnic inequalities in rectal cancer care are limited. OBJECTIVE: This study aimed to explore potential ethnic inequalities in rectal cancer care in the Netherlands. DESIGN: This was a nationwide, population-based observational study. SETTINGS: The study linked data of the Netherlands Cancer Registry with the Dutch population registry and the Social Statistics Database of Statistics Netherlands. Data were analyzed using stepwise multivariable logistic regression models. PATIENTS: All of the patients diagnosed with rectal carcinoma in 2003–2011 in the Netherlands (N = 27, 159) were included. MAIN OUTCOME MEASURES: We analyzed 2 rectal cancer treatment indicators (preoperative radiotherapy and sphincter-sparing surgery) and 2 indicators of short-term outcome of rectal cancer surgery (anastomotic leakage and 30-day postoperative mortality). RESULTS: Patients of Western non-Dutch and non-Western origin with rectal cancer were significantly younger and had a higher tumor stage than ethnic Dutch patients. Considering preoperative radiotherapy, anastomotic leakage, and 30-day postoperative mortality, no ethnic inequalities were detected. After adjustment for age, sex, disease characteristics, and socioeconomic status, Western non-Dutch and non-Western patients were significantly more likely to receive sphincter-sparing surgery than ethnic Dutch patients (OR = 1.27 (95% CI, 1.04–1.55) and OR = 1.57 (95% CI, 1.02–2.42)). LIMITATIONS: This study was limited by the relatively low numbers of non-Dutch patients with rectal cancer. CONCLUSIONS: Non-Dutch ethnic origin was associated with a higher rate of sphincter-sparing surgery. The absence of ethnic inequalities in preoperative radiotherapy, anastomotic leakage, and 30-day postoperative mortality suggests that ethnic minority patients have similar chances of optimal rectal cancer care outcomes as Dutch patients.